The Role of Commitment to Mediate Effect of Motivation on The Performance of Waste Bank Managers in The City of Denpasar - Made Winda; Putu Herny Susanti; Mirah Ayu Putri Trarintya (LAFADZ JAYA Publisher, 2022)
The purpose of this study was to analyze the role of commitment to mediate the influence of motivation on the performance of waste bank managers in Denpasar City. The research is causal in nature to provide an explanation and understanding of the relationship between the motivation variable and the manager's commitment and performance variables. The research population is all managers of Denpasar City waste bank which are still active, totaling 94 managers. The sampling technique was carried out using the saturated sample technique. Questionnaires that have been tested for validity and reliability were given to 94 respondents. Methods of data collection through: observation, interviews, documentation, and literature, questionnaires. The method of analysis using descriptive analysis and inferential analysis with Partial Least Square (PLS) analysis. The results of the study show that direct motivation significant positive effect on the commitment and performance of managers, and commitment plays a partial role in mediating the influence of motivation on the performance of managers. The research implication is the need for motivation to produce work according to standards. The research suggestion is that motivation needs to be increased again by giving awards to managers to form awareness to be more enthusiastic and motivated and committed to work so that they can improve performance at the Denpasar City Waste Bank.